Pengaruh Budaya Organisasi dan Kompensasi Terhadap Kinerja Pegawai (Studi Kasus Pada Kantor Kecamatan Pugung) - Aryadinata, Rehan (Jurnal EMT KITA, 2024)
This research aims to analyze the impact of Organizational Culture and Compensation on employee performance at the Pugung District Office. The research method used is descriptive quantitative with primary and secondary data. The research population involved 30 employees of the Pugung District Office. The instrument was tested for validity and reliability. Multiple Linear Regression Tests, the Statistical Test, the F Statistical Test, and the Coefficient of Determination Test are used to analyze the hypothesis. The research results show that there is a significant influence between Organizational Culture (X1) and Compensation (X2) on employee performance. The respective significance values are 0.000 (< 0.05) and 0.002 (< 0.05). This means that the higher the Organizational Culture and Compensation, the higher the employee performance. The simultaneous test results show that H3 is accepted, indicating the simultaneous influence of X1, and The remainder, amounting to 36.2%, is explained by other factors outside the research model.